Entrepreneurship marketing : principles and practice of SME marketing - Nwankwo, Sonny; Gbadamosi, Ayantunji (Abingdon, Oxon ; New York, NY : Routledge, 2020)
Small and medium-sized enterprises (SMEs) dominate the market in terms of sheer number of organisations; yet, scholarly resource materials to assist in honing skills and competencies have not kept pace. This well renowned textbook guides students through the complexities of entrepreneurship from the unique perspective of marketing in SME contexts, providing a clear grounding in the principles, practices, strategies, challenges, and opportunities faced by businesses today. SMEs now need to step up to the terrain of mobile marketing and consumer-generated marketing and utilise social media marketing tools. Similarly, the activities of various stakeholders in SME businesses like start-up accelerators, business incubators, and crowdfunding have now gained more prominence in SME activities. This second edition advances grounds covered in the earlier edition and has been fully updated to reflect this new, dynamic business landscape. Updates include: A consideration of social media imperatives on SME marketing; Discussion of forms of capital formation and deployment for marketing effectiveness, including crowdfunding; Updated international case studies drawn from diverse backgrounds; Hands-on practical explorations based on real-life tasks to encourage deeper understanding. This book is perfect for students studying SMEs, Marketing and Enterprise at both advanced undergraduate and postgraduate levels, as well as professionals looking to obtain the required knowledge to operate their businesses in this increasingly complex and turbulent marketing environment.
List of contributors -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Marketing -- Management; Entrepreneurship; Small business -- Management; New business enterprises -- Management; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Marketing / General